Extended delay in endoscopic mucosal resection is not associated with adverse outcomes: Findings from the COVID-19 pandemic - Liu, Eddie; McDonald, Cassandra; Son, Surim; Hawel, Jeffrey; Hussain, Nadeem; Khanna, Nitin; Yan, Brian; Jairath, Vipul; Sey, Michael (Endoscopy International Open, 2023)
Background and study aims The aim of this study was to investigate the impact of delayed endoscopic mucosal resection (EMR) of colorectal polyps on health outcomes.Patients and methods A bidirectional cohort study was completed. A baseline group consisting of all EMRs performed within a 15-month period before a province-wide, government-mandated cessation of EMR procedures due to the global pandemic was compared to EMRs impacted by the shutdown, defined as the COVID-19-delayed group. The primary outcome was the incidence of malignant polyps. Secondary outcomes included technical success, polyp recurrence at follow-up colonoscopy, advanced polyp histology, probability of meeting endoscopic criteria for adequate resection for malignant polyps, metastatic colorectal cancer, and complications.Results A total of 268 EMR procedures were included in the study cohort, of which 208 formed the baseline group and 60 were in the COVID-19-delayed group. The median (IQR) patient age was 72 (13.0) and 113 (41.2 %) were females. The median (IQR) wait time was 92 days (87.8) in the baseline group and 191 days (127.8) in the COVID-19-delayed group (P < 0.001). Overall, there were no significant differences in the incidence of malignant polyps, technical success, polyp recurrence on follow-up colonoscopy, advanced polyp histology, adequate endoscopic resection for malignant polyps, metastatic colorectal cancer, or complications between the two groups (P > 0.05 for all outcomes).Conclusions A longer wait time for EMR of colorectal polyps, increasing from a median of 92 to 191 days, was not associated with worse outcomes.